2019
DOI: 10.1186/s13058-019-1123-2
|View full text |Cite
|
Sign up to set email alerts
|

Separation of breast cancer and organ microenvironment transcriptomes in metastases

Abstract: Background The seed and soil hypothesis was proposed over a century ago to describe why cancer cells (seeds) grow in certain organs (soil). Since then, the genetic properties that define the cancer cells have been heavily investigated; however, genomic mediators within the organ microenvironment that mediate successful metastatic growth are less understood. These studies sought to identify cancer- and organ-specific genomic programs that mediate metastasis. Methods In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 51 publications
(42 reference statements)
4
40
0
Order By: Relevance
“…Alzubi et al demonstrated RNA sequencing data of human breast cancer tumors grown as PDXs at different sites in mouse and separated it into human (cancer) and mouse (microenvironment) transcriptomic datasets. They showed that the cancer transcriptome within PDX was affected by the microenvironment of the tumor implantation site [49]. Rashid et al utilized a syngeneic immunocompetent mouse model to show transcriptome differences between breast cancer tumors grown in MFP and subcutaneously [50].…”
Section: Discussionmentioning
confidence: 99%
“…Alzubi et al demonstrated RNA sequencing data of human breast cancer tumors grown as PDXs at different sites in mouse and separated it into human (cancer) and mouse (microenvironment) transcriptomic datasets. They showed that the cancer transcriptome within PDX was affected by the microenvironment of the tumor implantation site [49]. Rashid et al utilized a syngeneic immunocompetent mouse model to show transcriptome differences between breast cancer tumors grown in MFP and subcutaneously [50].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of previous RNA-sequencing data 42 revealed that about half of the genes encoding human targets of the 176 drugs are highly expressed in TNBC PDXs (Fig. 1b).…”
Section: Drug Screening Of Breast Cancer Pdxs Reveals Potential Targementioning
confidence: 99%
“…els of EGFR and BIRC5 were assessed using a PDX RNA-sequencing dataset 42 , as well as RNA sequencing data from two publicly available breast cancer cell line gene expression databases: the Harvard Medical School (HMS) Library of Integrated Network-based Cellular Signatures (LINCS) Breast Cancer Profiling Project (http://lincs. hms.harvard.edu/db/datasets/20348/) and the Broad Institute Cancer Cell Line Encyclopedia (CCLE) (https:// portals.broadinstitute.org/ccle).…”
Section: Analysis Of Egfr and Birc5 Gene Expression In Pdxs Cell Linmentioning
confidence: 99%
“…Consequently, the main application of PDX systems is to understand the molecular mechanisms of human cancers within controlled in vivo conditions. With the wide adoption of sequencing technologies, sequencing of PDX samples is now a standard (Turner et al 2018;Alzubi et al 2019;Girotti et al 2016;Li et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…To address the effect of mouse read removal in PDX sequencing data, we evaluated three strategies for preprocessing PDX Hi-C data: Direct, Xenome, and Combined. Using different library preparation strategies, we generated two deeply sequenced Hi-C datasets of a carboplatin-resistant UCD52 cell line (Turner et al 2018;Alzubi et al 2019). We further created three in silico PDX Hi-C datasets with either 10% or 30% of mouse read contamination, mirroring the percent of mouse reads observed in our experimental Hi-C data.…”
Section: Introductionmentioning
confidence: 99%